Systematics of a species complex in the deep-sea genus Eurycope, with a revision of six previously described species (Crustacean, Isopoda, Eurycopidae) - Wilson, George D. F. (University of California Press, 1983)
Bulletin of the Scripps Institution of Oceanography University of California, San Diego; v.25